Development of single phase PWM inverter for UPS application - Yaakob, Mohammad Ariff (2007)
This project is to develop an inverter circuit for Uninterruptable Power Supply (UPS) application. Inverters are circuit that convert DC to AC. The function of inverter is to create an AC voltage by using a DC voltage source and in UPS system, the voltage source that used DC voltage commonly batteries. Pulse-width modulation (PWM) technique is use in this project because with PWM, the amplitude of the output voltage can be controlled with the modulating waveforms. In this project, Metal Oxide Field Effect Transistor (MOSFET) is used as switch in the full bridge inverter circuit design. For alternated control purpose, sequential switching is designed for PWM get-way through the MOSFET driver. The function of the driver is to control the ON/OFF of the MOSFET. Driver of the MOSFET is essential in the inverter circuit because the driver use to interface between control circuits (low voltage) and inverter circuit (high voltage). The objective of this project is to develop single phase PWM Inverter for UPS application and to design the circuit, simulate and analyze the switching characteristic of single phase PWM inverter. The simulation of full-bridge single phase inverter for this project has been done by using Unipolar scheme and the output waveform is successfully generated. The switching process in hardware is control by PIC 16F877a and the MOSFET driver is using IR2110. At the end of this project, the results from simulation were compared with hardware.